Health dashboard for information management in cervical cancer screening - Adriana Aparecida Paz; Alloma Christine de Madureira Paula; Ananda Miranda de Lima; Gisele Lopes Castro; Mayara Casagrande Batista da Silva; Lunara Teles Silva (Revista Latino-Americana de Enfermagem, 2025)
Objective: to create a digital health dashboard for information management in the planning, monitoring, and evaluation of cervical cancer screening. Method* the study developed a technological production based on User-Centered Design, using fictitious data from cytopathological exams performed by women between 25 and 64 years old in Primary Health Care. The study complied with the requirements regarding copyright, ethics, and data protection. Results: the model was created on the Looker Studio® platform. The developed health dashboard is intended for use by nurses, professionals, and health managers. The dashboard’s usability simulations were carried out in fictitious cities. The dashboard optimizes access to information management in near real-time and presents a comprehensive health situation for health planning, monitoring, and evaluation. The model is reusable, which makes it a powerful tool for opportunistic and organized screening activities in the context of Primary Health Care. Conclusion* the health dashboard model as an information management tool allows nurses, professionals and health managers to make decisions to improve cervical cancer screening.